THE EFFECT OF TRAINING AND WORK DISCIPLINE ON EMPLOYEE WORK PERFORMANCE CONTROLLED BY SELF-CONCEPT, EDUCATION AND TRAINING AND WORK ABILITY AT THE MEDAN PALM OIL RESEARCH CENTER OFFICE - Sianturi, Rendy (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2025)
From the initial research that researchers did, as a researchinstitution that has an obligation in advancing the palm oilindustry in Indonesia, PPKS has a vision to become aninternational research institute capable of becoming a Center ofExcellence for national enterprises, who are capable of beingfinancially independent. and have quality and prosperous humanresources. Meanwhile the mission of PPKS is to uphold the palmoil industry in Indonesia through research and development andservices. Problems related to employee work performance aredecreasing at the Office of the Palm Oil Research Center (PPKS/ RISPA) which includes the completion of the work does notreach the target, work is neglected, not completing work on timeand employees often avoid being given work by superiorsbecause it is considered difficult to do the work. The purpose ofthis study was to determine whether training and work disciplinetogether have an effect on employee work performancecontrolled by self-concept, education and training, and workability at the Office of the Indonesian Palm Oil Research Center.The number of samples in this study amounted to 78 people.The analysis technique used is multiple linear regression. Theresults of the study show that training has a positive andsignificant effect on improving employee performance. Workdiscipline has a positive and significant effect on improvingemployee performance. Training and work discipline have asignificant effect simultaneously in improving employeeperformance. After controlling for self-concept, education andtraining and work ability, there were significant differences inemployee performance between training and work discipline (F =1.866; p <0.05) with effect size of 39.5% (0.395) with beforethere was control of self-concept, education and training andwork ability which was 0.294 (29.4%)